Interspeech 2017 2017
DOI: 10.21437/interspeech.2017-1066
|View full text |Cite
|
Sign up to set email alerts
|

Infected Phonemes: How a Cold Impairs Speech on a Phonetic Level

Abstract: The realization of language through vocal sounds involves a complex interplay between the lungs, the vocal cords, and a series of resonant chambers (e.g. mouth and nasal cavities). Due to their connection to the outside world, these body parts are popular spots for viruses and bacteria to enter the human organism. Affected people may suffer from an upper respiratory tract infection (URTIC) and consequently their voice often sounds breathy, raspy or sniffly. In this paper, we investigate the audible effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Table 3 shows the performance comparison of the proposed framework with the state-of-the-art methods using various phoneme segmentation on the URTIC database. Wagner et al [18] analyze the effect of common cold speech on a phonetic level. Phonemes are grouped into vowel, glide, consonant, liquid, stops, fricative, and nasal sounds, and the classification performance is evaluated using MFCC, invariant-integration features (IIF), and constrained maximum likelihood linear regression (CMLLR) feature.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 3 shows the performance comparison of the proposed framework with the state-of-the-art methods using various phoneme segmentation on the URTIC database. Wagner et al [18] analyze the effect of common cold speech on a phonetic level. Phonemes are grouped into vowel, glide, consonant, liquid, stops, fricative, and nasal sounds, and the classification performance is evaluated using MFCC, invariant-integration features (IIF), and constrained maximum likelihood linear regression (CMLLR) feature.…”
Section: Resultsmentioning
confidence: 99%
“…But UAR achieved using MFCC features extracted from VLR is low compared to the state-of-the-art methods. Wagner et al [18] examined the effects of common cold on phonetic level. They concluded that phoneme-level cold and healthy speech classification was not worthwhile.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, machine learning deals with the problem of designing algorithms that can automatically learn to detect patterns in data and allow a computer to make predictions based on what it has learned. In recent years machine learning methods have been applied successfully to solve various health-related recognition tasks [10,13,32] including stress detection [1,3,25]. Despite its continuously growing success the method is still subject to some caveats.…”
Section: Introductionmentioning
confidence: 99%